2004
DOI: 10.1074/jbc.m402385200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and Antibody Binding Studies of the Envelope Protein Domain III from the New York Strain of West Nile Virus

Abstract: The solution structure of domain III from the New York West Nile virus strain 385-99 (WN-rED3) has been determined by NMR methods. The West Nile domain III structure is a ␤-barrel structure formed from seven antiparallel ␤-strands in two ␤-sheets. One anti-parallel ␤-sheet consists of ␤-strands ␤1 In 2002, the mosquito-borne West Nile virus (WNV) 1 (family Flaviviridae, genus Flavivirus) was responsible for the largest outbreak of arthropod-borne encephalitis recorded in the Western hemisphere. In that year, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 24 publications
4
94
0
Order By: Relevance
“…Domain III of the WNV E protein has been documented recently to serve as the domain of the E protein that binds to cellular receptor integrin ␣ V ␤ 3 (6). Neutralizing Abs against WNV have been mapped to epitopes localized on the WNV E DIII (7)(8)(9)(10)(11). Therapeutic trials in mice with humanized anti-WNV E DIII Ab have also been shown to be highly effective in preventing WNV infection (9,10), suggesting that the recombinant WNV E DIII protein is an attractive vaccine candidate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Domain III of the WNV E protein has been documented recently to serve as the domain of the E protein that binds to cellular receptor integrin ␣ V ␤ 3 (6). Neutralizing Abs against WNV have been mapped to epitopes localized on the WNV E DIII (7)(8)(9)(10)(11). Therapeutic trials in mice with humanized anti-WNV E DIII Ab have also been shown to be highly effective in preventing WNV infection (9,10), suggesting that the recombinant WNV E DIII protein is an attractive vaccine candidate.…”
Section: Discussionmentioning
confidence: 99%
“…Crystallography data on the ectodomain of the flavivirus E protein revealed three distinct domains (DI, DII, and DIII) (3). The high antagonistic effect of recombinant WNV E DIII protein in blocking WNV infection in both mammalian and mosquito cells strongly suggested that WNV E DIII protein functions as the receptor-binding domain (4) and is responsible for the recognition and attachment to the cellular receptor (5)(6)(7). Importantly, a majority of the neutralizing epitopes have been mapped to the domain III region of the flavivirus E protein (8 -11).…”
Section: W Est Nile Virus (Wnv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Neutralizing epitope of dengue virus ED3 domains from DENV2, DENV3, DENV4, JEV and WNV, solved by nuclear magnetic resonance or X-ray crystallography, are similar (Kanai et al, 2006;Modis et al, 2003Modis et al, , 2005Nybakken et al, 2005;Volk et al, 2004Volk et al, , 2007Wu et al, 2003). Among the nine residues that belonged to the energetic epitope of mAb4E11 in ED3.DEN1-H6, six are different in YFV and seven in JEV and WNV (Table 3).…”
Section: Epitope Transplantationmentioning
confidence: 95%
“…Indeed, the E glycoprotein is the principal antigen that elicits neutralizing antibodies against flaviviruses. Many of the neutralizing epitopes are located in DIII of E and in close proximity to the conserved fusion loop in DII (20)(21)(22)(23)(24)(25)(26)(27)(28). E16 is a strongly neutralizing mAb against WNV that recognizes four polypeptide loops at the tip of DIII and inhibits infection primarily subsequent to cell attachment.…”
Section: W Est Nile Virus (Wnv) Causes a Febrile Illness In Humansmentioning
confidence: 99%